2023
DOI: 10.2337/db22-0557
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cell Infiltration Into Islets Without PD-L1 Expression Is Associated With the Development of Immune Checkpoint Inhibitor–Related Type 1 Diabetes in Genetically Susceptible Patients

Abstract: Immune checkpoint inhibitors (ICIs) could cause type 1 diabetes (T1D). However, the underlying mechanism remains unclear. We immunohistochemically analyzed pancreatic specimens from 3 cases with ICI-related T1D, and their histopathological data were compared those from 3 patients who had received ICI therapy but did not develop T1D (non-T1D) and 7 normal glucose-tolerant subjects as controls. All ICI-related T1D patients had susceptible HLA haplotypes. In ICI-related T1D, the β-cell area decreased and the α-ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…reported that although both DRB1*04:05-DQB1*04:01 and DRB1*09:01-DQB1*03:03 are frequent in Japanese fulminant T1DM, GAD antibody-positive fulminant T1DM was only significantly associated with DRB1*09:01-DQB1*03:03, even with considerably low GAD antibody positivity rates ( 14 ). As shown in Table 2 , DRB1*04:05-DQB1*04:01 has been detected in five cases, including ours ( 25 , 26 , 31 , 33 ). Yamaguchi et al.…”
Section: Discussionmentioning
confidence: 50%
“…reported that although both DRB1*04:05-DQB1*04:01 and DRB1*09:01-DQB1*03:03 are frequent in Japanese fulminant T1DM, GAD antibody-positive fulminant T1DM was only significantly associated with DRB1*09:01-DQB1*03:03, even with considerably low GAD antibody positivity rates ( 14 ). As shown in Table 2 , DRB1*04:05-DQB1*04:01 has been detected in five cases, including ours ( 25 , 26 , 31 , 33 ). Yamaguchi et al.…”
Section: Discussionmentioning
confidence: 50%
“…CPI-DM presents similarities with DM type I, as both entities result from humoral CPI-DM and cellular immune-mediated β-cell destruction leading to insulin deficiency. The immunohistopathological analysis of pancreatic tissue from patients with CPI-DM showed infiltration of islets with macrophages and T-lymphocytes, with a predominance of cytotoxic CD8 + T-lymphocytes, a decrease in b-cell area, and an increase in a-cell area compared to patients treated with CPI without presenting with DM and euglycemic controls, indicating selective targeting of β-cells [31]. Islet-antigen-specific CD8 + T-lymphocytes have also been identified in the peripheral blood of patients with CPI-DM [32].…”
Section: Discussionmentioning
confidence: 92%
“…The role of β cell PD-L1 in dampening the autoimmune attack through its interaction with the receptor PD-1 on immune cells is a highly engaging topic in the context of T1D treatment and islet transplantation, with studies reporting that the PD-L1/PD-1 interaction suppresses the adaptive immune response (61)(62)(63)(64)(65). Conversely, in humans, the use of immune checkpoint inhibitors (which block this interaction) increases the incidence of T1D in genetically susceptible populations (66,67), representing one of the more common immune-related adverse events associated with this therapy. Our studies show that blockade of PD-L1 using a monoclonal antibody accelerated diabetes onset in control NOD mice as expected.…”
Section: Discussionmentioning
confidence: 99%